Molecular characterization of non-polar sulfur compounds in the full boiling range crude oil fractions. (15th April 2023) - Wu, Jianxun; Ma, Chao; Zhang, Weilai; Chang, Weifeng; Zhang, Yahe; Shi, Quan
Graphical abstract: Highlights: A global view in molecular composition of sulfur compounds in the crude oil is presented. The high sulfur Iraq crude oil was fractionated into naphtha, middle distillate, and residual. GC-SCD, GC–MS, and FT-ICR MS were used for the molecular characterization. Thiophenes and sulfides with various carbon skeletons were quantitatively characterized. Abstract: Organic sulfur compounds (OSCs) are usually the most abundant heteroatomic compounds in crude oils and have very complex molecular composition. Thousands of sulfur-containing compounds have been identified from various petroleum fractions by different techniques. However, complete characterization of sulfur compounds in specific crude oils is rarely reported. In this study, molecular characterization of sulfur compounds in a whole crude oil was carried out with gas chromatographic and mass spectrometric techniques. The crude oil was separated into naphtha (<180 °C), middle distillate (180–350 °C), and the residual (>350 °C) by distillation. The naphtha was directly analyzed by gas chromatography coupled with a sulfur chemiluminescence detector. A methylation/demethylation method was carried out to separate aromatic sulfur compounds (ASCs) and sulfidic sulfur compounds (SSCs) from the middle distillate and the residue. The separated ASCs and SSCs were characterized by GC and mass spectrometry, as well as Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS). A global distribution of OSCs in the crude oil was obtained by the combination of the analysis results. The type and content of OSCs are significantly different among the distillation fractions. Hydrogen sulfide and mercaptans, accounting for 0.1 % and 1.2 % of the total sulfur content, respectively, mainly distribute in naphtha. SSCs, which are rich in thiadiamondoids, account for 15.5 % of the total sulfur content. ASCs are the most abundant identified species and account for 35.8 % of total sulfur content. Other OSCs such as complex polyheteroatomic compounds occupied 41.0 % of the total sulfur content.